Naringin attenuates fructose-induced NAFLD progression in rats through reducing endogenous triglyceride synthesis and activating the Nrf2/HO-1 pathway - Pengnet, Sirinat; Sumarithum, Phinsuda; Phongnu, Nuttaphong; Prommaouan, Sakdina; Kantip, Napapas; Phoungpetchara, Ittipon; Malakul, Wachirawadee (Frontiers in Pharmacology, 2022)
Background: Excessive fructose consumption causes hepatic lipid accumulation via increased triglyceride (TG) synthesis, leading to the development and progression of non-alcoholic fatty liver disease (NALFD). Naringin, a flavanone glycoside found in citrus fruit, has antioxidant and hypolipidemic properties. Therefore, the aim of this study was to investigate the effect of naringin on fructose-induced NAFLD in rats and the possible underlying mechanism. Methods: Male Sprague Dawley rats were given 10% (w/v) fructose in drinking water for 12 weeks. Naringin (100 mg/kg/day) was administered orally to rats for the last 4 weeks of fructose overload. After 12 weeks of treatment, the hepatic lipid content was determined. In addition, the expression of proteins involved in de novo lipogenesis (DNL) and TG synthesis as well as antioxidant and inflammatory mediators in the liver were examined by western blot analysis. Results: Treatment of fructose-fed rats with naringin significantly decreased the hepatic TG and cholesterol content as well as serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities. Naringin treatment also decreased the hepatic expression of carbohydrate response element binding protein (ChREBP), sterol regulatory element-binding protein-1c (SREBP-1c) and nuclear SREBP-1c (nSREBP-1c) as well as enzymes involved in DNL (acetyl CoA carboxylase [ACC] and fatty acid synthase [FAS]) and an enzyme involved in TG synthesis (glycerol-3-phosphate acyltransferase 1 [GPAT-1] and diacylglycerol acyltransferase2 [DGAT2]) in fructose-fed rats. In addition, naringin induced a significant decrease in the hepatic expression of nuclear factor kappa B (NF-κB) and tumor necrosis factor α (TNF-α). Furthermore, naringin administration restored the expression of the antioxidant mediators nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase-1 (HO-1) in the liver of fructose-fed rats.